Kualitas Pelayanan, Store Atmosphere Dan Harga Terhadap Kepuasan Konsumen Mie Gacoan (Studi Kasus Pada Mie Gacoan Manahan) - Joko Prasetyo; Burhanudin Ahmad Yani; Ida Aryati DPW (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to determine the effect of Service Quality, Store Atmosphere and Price on Consumer Satisfaction of Gacoan Manahan Noodles. This research uses a descriptive quantitative approach. The population in this study were all consumers of Manahan gacoan noodles, amounting to 975 people, the sample in this study was 100 people. The results of this study have a significant influence between Service Quality, Store Atmosphere and Price on Consumer Satisfaction of Gacoan Manahan Noodles. Keywords: Service Quality, Store Atmosphere, Price and Customer Satisfaction